Urban sociology of Göran Therborn - Titarenko, Larisa G. (Journal of the Belarusian State University. Sociology, 2019)
City as a focus of urban studies has become a scientific research topic more than hundred years ago. Sociologist Weber and historian Mumford constructed the basis of urban studies, while modern scholars gave multilateral analysis of the national capitals and the centers of global civilization in the XX century. Swedish sociologist Therborn, an author of new monograph «Cities of Power», presented the different cities – from the European capitals to the global agglomerations that symbolize the world power, as well as communist and post-communist citadels that at first had been constructed as a symbol of communist victory and then have been rebuilt in order to destroy the traces of the past that has sunk into oblivion. The monograph reveals various ways of elevating nation-states and tools of presenting their power, as well as social forces that determine the dynamics of urban development by their intertwining.
Keywords: city; power; nation state; global development